Rescuing memories: the toponym of the Cabeças neighborhood in Ouro Preto, Minas Gerais - Fernandes, Fernanda Kelly Mineiro; Mendes, Soélis Teixeira do Prado (Linha D’Água, 2023)
This paper aims to partly rescue the cultural memory of the eighteenth-century Vila Rica, currently known as Ouro Preto, Minas Gerais, by analyzing the toponym “Cabeças”, a name given to one of the oldest neighborhoods in Ouro Preto. Based on onomastic studies and on residents’ narratives, we have discussed aspects that go beyond linguistic data and that are present in the naming of toponyms. Data analysis shows that the geographic setting and the position of the location in relation to Vila Rica motivated the toponymic choice. Therefore, by recovering the historical, cultural, geographic, and social contexts that led to the creation of the toponym under analysis, it was possible to recover its meaning by shedding light on information underlying the name and in what situation in which it was given to the locality.